Prevalence of Eye Diseases and Visual Impairment In Urban Population - A Study from University of Malaya Medical Centre - Reddy, S.C.; Tajunisah, I.; Low, K.P.; Karmila, A.B. (Academy of Family Physicians of Malaysia, 2008)
One thousand one hundred and sixty-nine (1169) patients were examined in the Eye Clinic of University of Malaya Medical Centre over a period of three weeks to determine the prevalence of eye diseases and visual impairment. Age, gender, race, visual acuity and diagnosis of patients were noted from the case records. Cataract (385, 32.9%) was the most common eye disease seen in our study followed by glaucoma (274, 23.4%). Refractive errors were seen in 126 (10.8%) while diabetic retinopathy was noted in 113 (9.7%) patients. One hundred and fifteen (9.6%) patients had visual impairment and 11 (0.9%) had blindness in our study according to WHO classification of visual impairment. Refractive errors are the most common causes of visual impairment in children, while cataract, glaucoma and diabetic retinopathy account for visual impairment in elderly people. All these eye diseases are treatable and the severe eye conditions may be potentially preventable with early diagnosis.